ANALISIS KETERWAKILAN PEREMPUAN DALAM PEMILIHAN LEGISLATIF: Efendi, Atika Rahayu - M.Si, EFENDI,; Rahayu, Atika (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2021)
The representation of women in the legislative field, especially in the election of legislative members in 2019 is quite large and of course will provide balance and color the formulation of laws and regulations, budgeting and supervision with a gender perspective in Sungai Penuh City, so that the presence of women in the political arena is not only a formality. The formulation of the research problem, namely, how is the representation of women in the legislative elections (Case Study at the Sungai Penuh City DPRD 2019)? The research objective is to determine the representation of women in the legislative elections (Case Study at the River City DPRD 2019). This research uses a qualitative approach where data is obtained through field interviews with 5 informants referring to 4 research indicators, namely 1. Socialization 2. Recruitment. 3. Cadreization 4. Communication. The data obtained in the field were analyzed based on the classification of the informants' answers which were described in the results and discussion of the research which was then carried out by the interpreter of the researcher.It is known that the representation of women in the legislative elections (Case Study at the Sungai Penuh City DPRD 2019) from the four research indicators, none of them can represent the voice of women in the Sungai Penuh City DPRD. The lack of maximum presence of women in legislative elections so that they do not get vote support.